2014
DOI: 10.1016/j.jelekin.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Frequency analysis of lower extremity electromyography signals for the quantitative diagnosis of dystonia

Abstract: The purpose of this study was to develop an objective, quantitative tool for the diagnosis of lower extremity dystonia. Frequency domain analysis was performed on surface and fine-wire electromyography (EMG) signals collected from the lower extremity musculature of ten patients with suspected dystonia while performing walking trials at self-selected speeds. The median power frequency (MdPF) and percentage of total power contained in the low frequency range (%AUCTotal) were determined for each muscle studied. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The median power frequency (MdPF) and total power in low frequency were calculated for each muscle. The results revealed that MdPF for dystonic muscles had shifted to low frequencies and a concurrent increase in total power percentage in low-frequency range was observed [59]. Thus, frequency analysis of EMG signal not only provides us with distinction between normal and abnormal gait behavior but also specific gait abnormalities can be distinguished.…”
Section: Frequency and Time-frequency Analysismentioning
confidence: 90%
“…The median power frequency (MdPF) and total power in low frequency were calculated for each muscle. The results revealed that MdPF for dystonic muscles had shifted to low frequencies and a concurrent increase in total power percentage in low-frequency range was observed [59]. Thus, frequency analysis of EMG signal not only provides us with distinction between normal and abnormal gait behavior but also specific gait abnormalities can be distinguished.…”
Section: Frequency and Time-frequency Analysismentioning
confidence: 90%
“…It has been reported that the bandwidth of usable energy for surface EMG signals is between 20–500 Hz [25]. Further, this bandwidth is used in clinical research [26]. The sampling rate is in accordance with the Nyquist theorem, which states that the sampling rate must be greater than twice the highest frequency component of the analog signal.…”
Section: System Configurationmentioning
confidence: 99%
“…DAA-THA was performed on the right hip in 2014 at the Mayo Clinic in Rochester, MN. Based on the previously described standardized surgical technique [9] , an oblique incision was made over the anterior margin of the tensor muscle ∼2 cm lateral from the anterior superior iliac spine and extending 8-12 cm. The fascia of the tensor muscle was identified and incised.…”
Section: Case Historymentioning
confidence: 99%